(untitled) (Journal of Political Science and International Relationship, 2025)
Throughout history, Afghanistan has been a rising strategic hotspot, a link road between South and Central Asia for Energy resources and an uncertain place for power equations. With the decline of U.S. military engagement, Afghanistan has become a key strategic asset for superpowers to utilise for leverage. As emerging powers in the South Asian region, given the geopolitical importance and regional security, both China and India have been the obvious players in planning their strategic game inside Afghanistan. A cooperative venture between China and India in Afghanistan has depended mainly upon the mutual acceptance of strategic interests. This paper attempts to understand the strategic implications of U.S. military withdrawal from Afghanistan for China and India. Moreover, this paper will examine the policies and programs the two countries undertake to expand their respective importance. Apart from that, with the application of Defensive Realism as a theoretical framework, this paper deals with the emerging grounds and challenges before China and India to maintain a win-win situation in Afghanistan. the paper is expected to extract the results signifying the accommodative condition for both China and India in Afghanistan